Pleiotropic functions for transcription factor Zscan10 - Kraus, Petra; Sivakamasundari, V.; Yu, Hong Bing; Xing, Xing; Lim, Siew Lan; Adler, Thure; Pimentel, Juan Antonio Aguilar; Becker, Lore; Bohla, Alexander; Garrett, Lillian; Hans, Wolfgang; Hölter-Koch, Sabine; et al. (PLOS ONE, 2014)
The transcription factor Zscan10 had been attributed a role as a pluripotency factor in embryonic stem cells based on its interaction with Oct4 and Sox2 in in vitro assays. Here we suggest a potential role of Zscan10 in controlling progenitor cell populations in vivo. Mice homozygous for a Zscan10 mutation exhibit reduced weight, mild hypoplasia in the spleen, heart and long bones and phenocopy an eye malformation previously described for Sox2 hypomorphs. Phenotypic abnormalities are supported by the nature of Zscan10 expression in midgestation embryos and adults suggesting a role for Zscan10 in either maintaining progenitor cell subpopulation or impacting on fate choice decisions thereof.
Gesehen am 25.08.2020